UPAYA MENINGKATKAN PEMAHAMAN TENTANG PERANAN INFORMASI DALAM KUALITAS PRODUK DAN JASA PADA MATA KULIAH SISTEM INFORMASI MANAJEMEN MELALUI PENERAPAN METODE JIGSAW BAGI MAHASISWA POLITEKNIK UBAYA PRODI SEKRETARI ANGKATAN 2014 DAN 2015 - Slamet Wahyudi (Politeknik Ubaya, 2017)
In order to improve a classroom engagement in learning one specific lesson, for instance, in Management Information System (MIS) subject, certainly there is an extra effort need to be done. MIS originally is a quite technical lesson that requires adequate prior knowledge on Management and Information system. Clearly, MIS is something new for secretary study program students. As a lecturer, we need to shift from becoming the centre of learning rather than to lead students to become more active in the learning process (student - centered learning). In relation to that, a classroom action research (CAR) is needed urgently to help both lecturer and students running the class effectively. This time, the researcher tries to implement a Jigsaw learning type throughout two stages and phases. Hopefully, all students who learn one of MIS chapter which is about ‘The role of Information to increase product and service quality’ could understand the topic better than before using Jigsaw. Then, finally all secretary students who enrolled in this class could achieve a good mark in the final exam.